1994
DOI: 10.1111/j.1469-8749.1994.tb11897.x
|View full text |Cite
|
Sign up to set email alerts
|

The Crying Pattern of Korean Infants and Related Factors

Abstract: SUMMARY In.a study of 160 Korean infants aged between one and six months, average time spent sleeping decreased, and total daily maternal periods of contact increased, with age (though not significantly). The increment of total periods spent by the infant alone was significant, but the decrease of crying duration was not. There was no definite clustering of crying during the evening hours. The most common responses of mothers towards their baby's crying were feeding, contact and no response, in order of freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Two retrospective studies published from India and Brazil revealed colic prevalence of 16% and 16.3%, respectively [12,20] . In a prospective study of 160 Korean infants, no case of infantile colic was found [21] . Interestingly, the latter survey was adequate according to the quality criteria in this study as the researchers use a 24 h diary and a definition of infantile colic that included a time criteria [3] .…”
Section: Discussionmentioning
confidence: 96%
“…Two retrospective studies published from India and Brazil revealed colic prevalence of 16% and 16.3%, respectively [12,20] . In a prospective study of 160 Korean infants, no case of infantile colic was found [21] . Interestingly, the latter survey was adequate according to the quality criteria in this study as the researchers use a 24 h diary and a definition of infantile colic that included a time criteria [3] .…”
Section: Discussionmentioning
confidence: 96%
“…12,14,15 Although the modified Wessel criteria are widely used, firstly, normative studies in the general infant population are lacking 15 Secondly, considerable changes in infant care have occurred over the last 60 years since the Wessel criteria were published, 16,17 thus prevalence may be quite different than in the 1950s. Thirdly, while modified Wessel criteria have been used in different countries, the impact of cultural variations such as caregiving styles [18][19][20][21][22][23] and maternal soothing techniques 23,24 on the duration of infant fussing and crying may need to be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have focused on infant and toddler sleep patterns in Korea. One study of 160 Korean infants (birth to 6 months) found decreased sleep duration and increased maternal contact with increasing infant age, although this trend was non-significant ( 13 ). A more recent study utilizing the Nursing Child Assessment Sleep/Activity Record in a sample of Korean infants ages birth to 6 months (n = 94), provided limited data on average sleep duration, night wakings, and maternal behaviors regarding infant sleep ( 14 ).…”
Section: Introductionmentioning
confidence: 99%